(untitled) (Религиски дијалог и соработка, 2025)
Following the interpretation of the famous Croatian sociologist Željko Mardešić (Jakov Jukić), this paper analyzes secularization in the context of contemporary sociology of religion. Considering various social, cultural, and religious changes, the presented secularization process is the origin of the sudden and unexpected flourishing of various forms of new religiosity and the alarming appearance of relics of the past, i.e., the increasingly present fundamentalism and integralism in major religions. According to Željko Mardešić, the secularization process consists of three levels and includes society, the Church, and – most deeply – the individual person. The individual finds themselves in a strange gap. On the one hand, secularization swallows up and annuls the sacred, while, on the other hand, the individual produces the sacred, which is not a substitute for traditional religion, but something completely new and opposed. Željko Mardešić sees the future of Christianity following in the footsteps of the Second Vatican Council, which seeks the effort of sincere questioning its state on the part of Christianity; to choose either political religiosity or authentic religiosity with no political security. It is important to note that Christianity, deprived of its many worldly roles, in the new secularization context is encouraged to focus on ritual celebration and spiritual immersion to creatively transform society and cultural life. In this context, there emerges an increasingly acceptable interpretation according to which, using Željko Mardešić’s words, secularization is seen as a happy event for historical Christianity, because it draws Christianity a little closer to the original evangelical truth and a more authentic living of the goodness of its members. This event manifests in rejecting the collectivist and ideological vision of Christianity and advocates accepting the light of goodness rather than one’s own group, supporting freedom and the free human in a group defined by the community of people who believe in the person and teachings of Jesus Christ.